Influence of principal point on camera calibration algorithms - Sirisantisamrid, Kaset; Tirasesth, Kitti; Matsuura, Takenobu (My University, 2009)
The principal point has influence on the camera parameters determined by most calibration algorithms in which the camera parameters are inaccurate and unstable when the principal point is shifted from the center of image. This paper proposes a simple technique for camera calibration that is insensitive to change the principal point and shows an influence of principal point on camera calibration algorithms. The proposed method starts from defining a set of intermediate parameters in terms of camera parameters. Then, the intermediate parameters, the lens distortion coefficients, the principal point, and the distances between sensors are iteratively computed. Finally, the remaining camera parameters are estimted from the obtained intermediate parameters. In the experimental results, we tested the influence of principal point on camera parameters computed by the proposed method and compared the results with the conventional method.
Keywords: Calibration algorithms; Camera parameters; Intermediate parameters; Principal point